Kebermaknaan Hidup Pada Pelaku Homoseksual Yang Telah Membuka Jati Diri - Fitriana, Nurul; , Dr. Moordiningsih, M. Si, Psi (2017)
The process to open this identity becomes very difficult and very stressful for homosexuals, when family and friends react negatively. It makes homosexuals can not necessarily revealing their identities. This study aims to understand and describe the meaningfulness of life in the homosexual identity that has opened. In this study, the authors use the case study method. The method used in this research is interview and observation. The informant is one person, male sex, who have realized the sexual perversion that happened to him since the age of 14 years. Meaningfulness of life possess unique properties, which means that the meaningfulness of life can differ from one person to another. Informants felt quite happy with the achievement that he can live up to now, achieving the life that makes him happy are the things that comes to the material. While the purpose of life he wants to achieve is to have a better life with a family.